Preceitos constitucionais e uniões simultâneas: a (im)possibilidade de reconhecimento com base nos fundamentos da ADPF 132 e do Tema 529 - Silva Neto, Júlio Marques da (2022)
The present study is about the possibility of recognition as family entities of two or more stable unions that are constituted simultaneously with the presence of a common denominator among them. The theme is relevant due to the proliferation of families constituted in this way and the demand for positioning of the national Courts. In order to carry out the study, it is resort to the aggregated judgment of ADPF 132 and ADI 4277 carried out by the STF in 2011, extracting from there the fundamental principles and rights that allowed the legal recognition, in the light of Family Law, of same-sex unions. It is verified, then, that these elements also authorize the recognition of simultaneous unions. Afterwards, the decision of the STF in Theme 529 that denies the legal validity of simultaneous unions based on monogamy is analyzed, proceeding to a confrontation of monogamy with the constitutional axiological table, in particular the foundations extracted from ADPF 132, whose conclusion demonstrates that monogamy lacks from a principled nature and, therefore, cannot be imposed indiscriminately to all family arrangements, which is why the recognition of simultaneous unions as family entities is understood to be possible. The methodology used in the mentioned evaluations was the case study, as well as the inductive method.